Hubungan Sikap dengan Pemeriksaan Payudara Sendiri di Kawasan Pesisir Telaga Ratu Kairatu - Mayasari, Windatania (Lembaga Dongan Dosen, 2024)
Cancer Bosom Represent AN Condition Of Where Cell Have Losing Of Operation And Normal Mechanism of him, Quickly And Do Not In Control That Happened At Network Bosom. Method of Peneltian Analytic Descriptive With Approach Of Cross-Sectional Technicsly Random Sample Instrument Research Using Data-Processing Kuesioner With SPSS And Use Test of Chi-Square With This Subyek Peneltian Is Woman at Telaga ratu Kairatu Counted 70 Responder. Please Conclude That Ho Refused And Is Ha Accepted By There Are Relation Which Is significant Attitude About Cancer Bosom With Inspection Of Bosom Alone At Woman Telaga Ratu Kairatu